2023
DOI: 10.1109/tte.2022.3177296
|View full text |Cite
|
Sign up to set email alerts
|

Dual Model Predictive Controlled Hybrid Energy Storage System for Naval DC Microgrids

Abstract: Hybrid energy storage system (HESS) is an effective measure to improve the electrical performance of naval DC microgrids supplying power pulsed loads (PPLs). Coordination control scheme and capacity configuration of the HESS are two key issues to meet multiple control objectives and constraints. In response to the requirements of optimal operation for HESS under various complex scenarios, a dual model predictive control (D-MPC) strategy is proposed for the HESS integrated with the superconducting magnetic ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The authors concluded through a simulation and experiment validation that the fluctuation in DC link voltage was reduced, and the battery and supercapacitor's coordinated function lessened the battery's stress. In [62], a dual model predictive control (D-MPC) technique for a hybrid energy storage system (HESS) coupled with superconducting magnetic energy storage (SMES) and a battery in naval DC microgrids was used to meet pulsed power demands.…”
Section: Hybrid Energy Storage Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded through a simulation and experiment validation that the fluctuation in DC link voltage was reduced, and the battery and supercapacitor's coordinated function lessened the battery's stress. In [62], a dual model predictive control (D-MPC) technique for a hybrid energy storage system (HESS) coupled with superconducting magnetic energy storage (SMES) and a battery in naval DC microgrids was used to meet pulsed power demands.…”
Section: Hybrid Energy Storage Systemsmentioning
confidence: 99%
“…In such applications, the flexibility and adaptability of an HESS prove instrumental in maintaining grid integrity and ensuring reliable performance, making it an indispensable asset for the evolving landscape of DC microgrids. Several research studies have been conducted to analyze the impact of HESSs on power systems [61][62][63][64][65][66][67][68][69][70][71].…”
Section: Hybrid Energy Storage Systemsmentioning
confidence: 99%
“…The MPC tertiary controller analyzes the demand forecast and operational cost data. It develops an ESS dispatch schedule and feeds the output signal to a secondary controller [80]. The secondary control is based on real-time measurements of the active and reactive powers.…”
Section: Microgrids Tertiary Control: Mpc-based Economic Optimizationmentioning
confidence: 99%
“…A similar employment of SMES for marine power systems was also found in [8], where the authors exploited this storage technology to control the DC bus voltage of a power converter under peak load conditions. A possible application of SMES can also be found in naval DC microgrids, where modelpredictive control strategies for the ESS have been implemented for efficiently managing the available energy, with particular reference to pulsed-power load supply [9].…”
Section: Introductionmentioning
confidence: 99%